PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS II SDN 126 PEKANBARU - Aulia Khairani; Hariati Azizah; Nafisah; Resty Amelia Putri; Veny Lusiana; Mahmud Alpusari; Muhammad Febriyan Setiana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to improve the learning outcomes of mathematics subjects of class II students of SDN 126 Pekanbaru by implementing the Problem Based Learning (PBL) model. This study uses a stage method according to the Kemmis and Mc Taggart model, there are stages in 1 cycle such as planning, action, observation, and reflection. The technique of collecting student learning outcome data is by giving a written test after PBL-based learning and observing learning during the research process. The value in cycle 1 shows a percentage of completion of 50%, the results have not met the KKM value of 80%. Then, in cycle 2 shows an increase in the percentage of completion to 78%. In cycle 3 the percentage of completion increased to 90%, the results have met the specified KKM value. Based on the results of the study, it can be concluded that the application of the PBL model can improve the learning outcomes of class 2 students of SDN 126 Pekanbaru.